Response of Chinese Wheat Germplasms to Different Levels of Nitrogen, Phosphorus and Potassium - Khalid Mahmood; Sumayya Bibi; Laiba Farid; Faiza qadeer; Ali Hassan; Saira Gohar; Atiq Ur Rahman; Moien Ur Rehman Abbasi; Shamsur Rehman; Emaan Noor (International Journal of Advanced Technology and Social Sciences, 2023)
Pakistan's average wheat production is significantly lower than that of the rest of the world, including adjoining countries like India and China. NPK are the major primary nutrients needed by the plants in large amount. Optimum amount of these nutrients has to be maintained in soil for achieving the maximum wheat yield. High yielding varieties of wheat have high nutritional requirements and generally give prominent response to the applied levels of NPK. Field research entitled “Response of Chinese wheat lines to different levels of NPK” was conducted at Agronomy Research Farm, The University of Agriculture Peshawar during Rabi season 2021-2022. The research was carried out in randomized complete block design (RCBD) having three replications. Treatments were consisted of Chinese wheat lines (MY-1501, MY-1416, MY-1419, MY-902,15CA73, JM-1683J, MY-1215, MY-2914 and MY-409) and two NPK levels (F1: 120-90-60 and F2: 240-180-120 kg ha-1). The results of the experiment indicated that wheat line JM-1683 maintained higher number of tillers (385 m-2) and number of spikes (360 m 2).While higher. MY-15CA73 produced higher thousand grains weight (47.682 kg ha-1). MY-1419 produced higher biological yield (11433 kg ha-1). MY-1419 produced higher grain yield (4779.3 kg ha-1). Wheat germplasms with the application of NPK at the rate of 240-180-120 kg ha-1 produced maximum number of tiller (385 m-2), number of spikes (347 m-2), thousand grain weight (41.955 kg ha-1), biological yield (10068 kg ha-1) and grain yield (4271.7 kg ha-1) followed by lower level of NPK (120-90-60 kg ha-1). It is concluded that wheat lines MY-1419 produced higher grain yield with the application of NPK at the rate of 240-180-120 kg ha-1 and is therefore recommended